PELAKSANAAN POLA PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS IIA BENGKALIS DALAM TAHAP ASIMILASI - Arif Rahman; Erdianto Erdianto; Elmayanti Elmayanti, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Literally, prisons are places to carry out coaching for prisoners andcorrectional students. The guidance that has been carried out by each prisongenerally includes matters of spiritual development, education, skills, and themain thing is to rebuild his confidence to be able to re-integrate with the outsidecommunity after completing his criminal period. The implementation of guidancecarried out by prisons for inmates of course refers to the laws and regulationsgoverning it, because in the implementation of coaching there are severalprinciples that should not be violated.This type of research can be classified in the type of sociological lawresearch (empirical), because in this study the author directly conducts researchon the location or place under study in order to provide a complete and clearpicture of the problem being studied. This research was conducted at theCorrectional Institution, while the population and samples were the Head of ClassII A Bengkalis Correctional Institution, the Head of the Registration Subsidy ofthe Class II A Bengkalis Correctional Institution and the Assimilation StageInmates at the Class II A Bengkalis Correctional Institution.The conclusions that can be obtained from the results of the research are:First, the Implementation of the Pattern of Guidance for Convicts at the Class II ABengkalis Correctional Institution in the Assimilation Stage is divided into severalstages, one of which is initial coaching which is preceded by a period ofobservation, research and introduction to the environment (mapenaling). Second,the Factors and Constraints in the Convict Assimilation Guidance System at theClass II A Bengkalis Correctional Institution, namely the problem starting fromthe pattern of giving assimilation related to recidivist prisoners unable to carryout assimilation, convicts who carry out fines cannot carry out assimilation.Third, the Efforts Made to Overcome the Obstacles That Appear in theAssimilation Guidance System at the Class II A Bengkalis CorrectionalInstitution, such as regarding the schedule of inmates who work with third parties.Keywords: Prisoners, Assimilation, Correctional Institutions, DevelopmentPatterns.